The Potential of Distributed Energy Resources in Building Sustainable Campus: The Case of Sichuan University. (July 2018) - Zhu, Yingming; Wang, Fu; Yan, Jinyue
Abstract: Distributed energy resources systems are decentralized, modular and more flexible technologies. These systems can comprise multiple generation and storage components. Sichuan University (SCU) has joined Global Urban Development program, and takes part in Sustainability Tracking, Assessment & Rating System, aims at a sustainable campus. So we investigated the potential of distributed energy resources, e.g. solar power, that can be used in SCU. Firstly, we build 4 micro-grids with a total 156 Kw PV capacities to collect the power generation data. The total roof area of SCU Jiangan campus is 165701 m 2, and the estimated installed capacity is 8.3MW-11.6MW. Based on this data, 33% ~ 46% power cost can be covered by PV power generation.